The Influence Of The Ability In Mastering Dialogue On Students Speaking Comprehension At SMP SWASTA CINTA RAKYAT 3 Pematangsiantar - Ridwin Purba; Willy Febrianto Samosir (Program Studi Pendidikan Bahasa Inggris FKIP, 2022)
The aim of this research was to find out the influence of the ability in mastering dialogue on students speaking comprehension at SMP SWASTA CINTA RAKYAT 3 PEMATANGSIANTAR in the academic year of 2021/2022. This research was classified as a true-experimental study. It involved 24 students from two groups, as the experimental group (12 students) and as the control group (12 students). The experimental group was students taught using picture sets dialogue where as the control group was students taught using lecture technique. The data were obtained by using pre-test and post-test. The data of the pre-test and post-test of both groups were analyzed by using descriptive and inferential statistic. (SPSS 22.0). The result of the research shows that the testing hypothesis of post-test score, it is found that tcount (9,326) > ttable (8,233) at the significance level a = 0.05 and degrees of freedom (df) = 11. H0 is rejected and Ha is accepted. So, it means that the influence of the ability in mastering dialogue significantly on students speaking comprehension at SMP SWASTA CINTA RAKYAT 3 PEMATANGSIANTAR academic year of 2021/2022